SOME DETERMINANTS OF ECONOMIC DEVELOPMENT IN SOUTH CROATIA IN THE INTERWAR PERIOD: DUBROVNIK AND KORCULA DISTRICTS CASE - Penava, Marija Benic (European Scientific Journal, ESJ, 2014)
The paper examines the territorial changes that have affected Dubrovnik and Korčula districts between the two world wars, as well as some characteristics of the economy in this area. By becoming a part of the Kingdom of Serbs, Croats and Slovenes, southernmost Croatia was further isolated from the European core, and thus from modern economic trends. Therefore, the dominant Dalmatian agrarian economy with its lagging traditional system known as ‘settlers’, with its extremely divided land property, prevented competitiveness of agricultural products in the new market conditions. At the same time, a high proportion of workers in agriculture, a lack of skilled labour and a high illiteracy had significantly reduced the possibilities of the workers being the source of economic growth; which together with a lack of capital and technological progress restricted economic development in southern Croatia. Analyses of the structure and the cultivation of land in the Croatian far south indicates the reasons for an inclination of the population towards service industries in the districts of Dubrovnik and Korčula, which has been preserved in the structure of the economy today.